Efektivitas Gel Ekstrak Biji Kopi Robusta (Coffea canephora) terhadap Peningkatan Jumlah Fibroblas pada Penyembuhan Luka Pasca Gingivektomi - Nailah Rahmadani; Melok Aris Wahyukundari; Happy Harmono (Fakultas Kedokteran Gigi Universitas Jember, 2022)
Gingivectomy is a surgical procedure aimed at eliminating pseudo pocket in gingival hyperplasia, and also to obtain a good gingival margin aesthetic. The process of wound healing after gingivectomy takes a long time. Fibroblasts are cells that takes an important role in the process of wound healing. One alternative treatment giving medication by applying Robusta coffee bean extract gel which acts as an anti-inflammatory and antioxidant in the wound healing process. The objective was to determine the potential and optimal concentration of Robusta coffee bean extract gel to increase the number of fibroblast cells in post-gingivectomy wound healing phase. This study used 32 male wistar rats were divided into 4 groups. All male wistar rats were treated with gingivectomy in the left mandibular first molar tooth area. The first group as a negative control did not apply any drug, the second group applied 40% robusta coffee extract gel, the third group applied 50% robusta coffee extract gel, and the fourth group 60% robusta coffee extract gel was applied. On the 3rd and 7th day, the experimental animals in all groups were decapitated to do a histological examination of fibroblasts in post-gingivectomy wounds phase. The result showed that applied robusta coffee extract gel present higher number of fibroblasts than the negative control group. The group of 40% dan 50% shows a significant difference of the number of fibroblasts on the 3rd and 7th day. The conclusion was robusta coffee bean extract (Coffea canephora) potential to increase the number of fibroblasts in wound healing phase after gingivectomy, with an effectivity concentration of 40% and 50%.